PENGEMBANGAN SPIN WHEEL DENGAN KARTU TANTANGAN BUDAYA DAERAH INDONESIA UNTUK MENINGKATKAN JOYFUL LEARNING DAN HASIL BELAJAR PENDIDIKAN PANCASILA MURID KELAS V SEKOLAH DASAR (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The issue with Pancasila education in the fifth grade at SDN Drajidan is that the curriculum is dominated by lengthy texts, causing students to become bored, which has resulted in 37.5% of students failing to meet the minimum competency standards. This study aims to develop a spin wheel activity using cards featuring challenges related to Indonesian regional cultures to enhance joyful learning and academic achievement. The research employed an R&D approach using the ADDIE model. Validators consisted of subject matter experts and media experts. Teachers provided feedback, while students served as subjects for assessing improvements in learning outcomes and joyful learning. Data were collected through interviews, needs and feedback questionnaires, and pretest-posttest assessments. The results of the study indicate that the developed product falls into the “acceptable” category with an 80% rating from the content expert, and the “highly acceptable” category with a 96.47% rating from the media expert. There was an increase in joyful learning and student learning outcomes, as evidenced by pretest-posttest scores and initial and final joyful learning questionnaires. The effectiveness on learning outcomes was demonstrated by the N-Gain scores of 0.8854 for the small group and 0.8875 for the large group. The effectiveness regarding joyful learning is indicated by the N-Gain results of 0.9562 for the small group and 0.8881 for the large group. Based on the N-Gain test results, it can be concluded that the media is highly effective in enhancing joyful learning and student learning outcomes in Grade 5 at SDN Drajidan.